2020
DOI: 10.1111/jdi.13226
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels, prediabetes risk and hemoglobin A1c levels in young non‐diabetic Saudi women

Abstract: Aims/Introduction Vitamin D levels are negatively correlated with prediabetes risk and hemoglobin A1c levels in individuals with prediabetes. The data are, however, scarce and inconsistent among different populations. We aimed to assess the association of vitamin D with prediabetes risk and hemoglobin A1c levels in young Saudi women with normoglycemia and prediabetes. Materials and Methods We analyzed the data of individuals without diabetes (without diabetes history and hemoglobin A1c <6.4%) from the Princess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(79 reference statements)
1
1
0
Order By: Relevance
“…Gioreli et al didn't find any association of vitamin D with fasting and 2H-OGTT glucose values33 . No correlation between HbA1c and vitamin D was also found by other studies20,22 . Data from the National Health and Nutrition Examination survey found a negative correlation between vitamin D level and HbA1c among US adults of a specific age group who reported them as free from DM34 .…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Gioreli et al didn't find any association of vitamin D with fasting and 2H-OGTT glucose values33 . No correlation between HbA1c and vitamin D was also found by other studies20,22 . Data from the National Health and Nutrition Examination survey found a negative correlation between vitamin D level and HbA1c among US adults of a specific age group who reported them as free from DM34 .…”
supporting
confidence: 62%
“…However, this IFG group might have IGT simultaneously 19 . Based on HbA1c, one study did not find any significant difference of mean vitamin D level in a group of young women with prediabetes 22 . One study found significantly higher mean vitamin D level and lower serum calcium level in the people of NGT group that were not consistent with our findings 23 .…”
Section: Discussionmentioning
confidence: 94%